Sildenafil 4.0-Integrated Synthetic Chemistry, Formulation and Analytical Strategies Effecting Immense Therapeutic and Societal Impact in the Fourth Industrial Era - Andreas Ouranidis; Anastasia Tsiaxerli; Elisavet Vardaka; Catherine K. Markopoulou; Constantinos K. Zacharis; Ioannis Nicolaou; Dimitris Hatzichristou; Anna-Bettina Haidich; Nikolaos Kostomitsopoulos; Kyriakos Kachrimanis (MDPI AG, 2021)
Sildenafil is a potent selective, reversible inhibitor of phosphodiesterase type 5 (PDE5) approved for the treatment of erectile dysfunction and pulmonary arterial hypertension. Whilst twenty years have passed since its original approval by the US Food and Drug Administration (USFDA), sildenafil enters the fourth industrial era catalyzing the treatment advances against erectile dysfunction and pulmonary hypertension. The plethora of detailed clinical data accumulated and the two sildenafil analogues marketed, namely tadalafil and vardenafil, signify the relevant therapeutic and commercial achievements. The pharmacokinetic and pharmacodynamic behavior of the drug appears complex, interdependent and of critical importance whereas the treatment of special population cohorts is considered. The diversity of the available formulation strategies and their compatible administration routes, extend from tablets to bolus suspensions and from per os to intravenous, respectively, inheriting the associated strengths and weaknesses. In this comprehensive review, we attempt to elucidate the multi-disciplinary elements spanning the knowledge fields of chemical synthesis, physicochemical properties, pharmacology, clinical applications, biopharmaceutical profile, formulation approaches for different routes of administration and analytical strategies, currently employed to guide the development of sildenafil-based compositions.